Peningkatan Motivasi dan Prestasi Belajar Matematika dengan model 3N Kelas X SMK Muhammadiyah 3 Yogyakarta - Nurul Hidayat; Benedictus Kusmanto (UNION: Jurnal Ilmiah Pendidikan Matematika, 2018)
The purpose of this research is to improve the motivation and achievement of learning mathematics students of class X SMK Muhammadiyah 3 Yogyakarta with 3N model. The subjects of the study were students of class X TITL at the school. The object of research is the whole process on the application of mathematics learning with 3N learning model in the mathematics lessons in that class. Data collection using questionnaires and test questionnaires to determine the changes that occurred before and after the application of the learning model. Data analysis techniques use descriptive techniques average and percentage. The average percentage of student's motivation in the first cycle of 69.06% increased to 78.90% in cycle 2. While the average achievement of students in cycle 1 of 81.39 with a complete percentage of 66.67% increased to 84, 02 with a percentage of 83.33% completeness in cycle 2. Thus it can be concluded that 3N learning model can improve the motivation and achievement of learning mathematics students of class X SMK Muhammadiyah 3 Yogyakarta academic year 2017/2018.